The role of endoscopic ultrasound in the staging of tracheal neoplasm: a brief review - Oliveira,Cristiane Mota (2019)
SUMMARY Our case report shows the complexity of dealing with tracheal tumors, highlighting the importance of the method used for staging. In this report, endoscopic ultrasound (EUS) was crucial to identify the involvement of the esophageal muscular propria in a tracheal tumor and change the surgical planning of the case. Staging this kind of tumor represents a challenge for physicians. There is no evidence in the literature on which methods represent the gold standard for T staging.